Plyometric Based Training on Athletes' T Kick Speed Perisai Diri - Martina Dewi Lengo; Carles Nyoman Wali; Gregorius Gordianus Jado; Paulus Natalis Nggaa (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2023)
The training model in improving a pencak silat athlete's abilities is an important factor, because an inappropriate training model will have a bad impact on the technique being trained. For example, the training model given to the fighters is not varied or is interpreted as a monotonous training method, this has a direct impact on the fighters, for example they are lazy about training and do not experience changes. The aim of this research was to determine the effect of plyometric training on the speed of T kicks in silat martial arts at the 1945 Teachers' Association University, East Nusa Tenggara. In this research, researchers used a one-group pre-test and post-test design with a quantitative experimental method approach. The number of samples in this study was 20 martial artists. Data collection techniques in this research used tests and non-tests. Non-tests include observation, interviews and documentation, then the test method uses two plyomteric training methods. The data analysis technique in this research uses the t-test analysis system. The results of this research prove that based on the results of the calculation of the data in this study, it shows that there is a change in the speed of the T kick in the fighters. With the posttest results, if you look at the pre-test average, it is 21.93 and the post-test value is 23.86%. Based on these results, it was stated that there was an influence of plyometric training, the form of training of which was squat split jump and stride jump crossover, the speed of Pencak Silat T kicks. Based on the categorization of the final test results, the speed of Pencak Silat T kicks performed by the silat fighters was in the Good category.